Multiplicity dependence of σψ(2S)/σJ/ψ in pp collisions at √s = 13 TeV - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Cocha Toapaxi, Carlos; De Cian, Michel; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; Langenbruch, Christoph; Leverington, Blake; et al. (Journal of high energy physics, 2024)
The ratio of production cross-sections of ψ(2S) over J/ψ mesons as a function of charged-particle multiplicity in proton-proton collisions at a centre-of-mass energy √s = 13 TeV is measured with a data sample collected by the LHCb detector, corresponding to an integrated luminosity of 658 pb−1. The ratio is measured for both prompt and non-prompt ψ(2S) and J/ψ mesons. When there is an overlap between the rapidity ranges over which multiplicity and charmonia production are measured, a multiplicity-dependent modification of the ratio is observed for prompt mesons. No significant multiplicity dependence is found when the ranges do not overlap. For non-prompt production, the ψ(2S)-to-J/ψ production ratio is roughly independent of multiplicity, irrespective of the rapidity range over which the multiplicity is measured. The results are compared to predictions of the co-mover model and agree well except in the low multiplicity region. The ratio of production cross-sections of ψ(2S) over J/ψ mesons are cross-checked with other measurements in di-lepton channels and found to be compatible.
Gesehen am 08.01.2026
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, C. Cocha Toapaxi, M. De Cian, F. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und zahlreiche weitere]